ANALYSIS OF SOME PHYSICOCHEMICAL PROPERTIES OF EFFLUENTS AND RAW WATER FROM CHALLAWA TEXTILE INDUSTRY, KANO STATE, NIGERIA - IBRAHIM, D; PAUL, E. D; YASHIM Z. I, (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY (2536-6041), 2019)
Assessment of some physicochemical properties and raw water of Challawa Textile Industry Kano, State, Nigeria revealed that some of the effluents are highly impacted at the discharge point than the upstream and downstream; for instance, the pH, 11.14mg/l, total solids (TS), 520mg/l and total dissolved solids (TDS), 500mg/l but restored to normal downstream to 7.15, 170mg/l, 40mg/l respectively. However, the chromium (Cr), 0.74ppm copper (Cu) 0.43ppm and zinc (Zn) 6.33ppm contents of water from the effluents recipient river were greatly increased to levels much higher than are considered safe to the environment and human health